(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-65-78 Abstract. The analysis of song, being an important component of the culture of any ethnic group, is an essential factor of globalization processes in their cultural and linguistic dimension and arouses interest in modern humanitarian knowledge. This article analyzes the representations of linguistic and cultural identity and collective memory within the framework of the Spanish-language song discourse of different periods of time, which allows us to trace and comprehend whether the symbolic load and the national-cultural specifics of the products of song discourse have changed over time. The conducted research made it possible to make sure that the texts of musical compositions can be a kind of manifestation of national identity and can reflect elements of collective memory, which is largely associated with the identity and value orientations of native Spanish speakers. Key words: song discourse, music, collective memory, linguocultural identity, mass culture, globalization, Spanish, latinx community